OP18 Disease course of Crohn's disease during the first ten years following diagnosis in a prospective European population-based inception cohort – the Epi-IBD cohort. (30th January 2023) - Wewer, M D; Salupere, R; Kievit, H A L; Nielsen, K R; Midjord, J; Domislovic, V; Krznarić, Ž; Pedersen, N; Kjeldsen, J; Eriksson, C; Halfvarson, J; Talbot, A; et al.
Abstract: Background: The Epi-IBD cohort is a prospective European population-based cohort of 1, 390 patients diagnosed in 2010 and 2011 with inflammatory bowel disease (IBD) according to Copenhagen criteria in centres from Eastern and Western European countries. The study aims at describing differences in incidence, treatment strategies, disease course and prognosis of Crohn's disease (CD) across Eastern and Western Europe. Methods: CD patients were followed prospectively from the time of diagnosis until December 31 st, 2020, death, emigration or loss of follow-up. Clinical data on surgery, hospitalizations, and medical treatment, were captured throughout the follow-up period and entered into a validated web-database, www.epi-ibd.org . Associations between surgery and covariates were analysed by multivariate Cox regression analyses. Results: In total, 482 CD patients aged ≥15 years from 21 centres in 5 Eastern and 11 Western European countries were included. At 10-years follow-up, 101 (21%) patients underwent first intestinal resection and 11 out of these 101 patients (11%) underwent additional resections. Furthermore, 176 (37%) patients had at least one CD related hospitalization. Cancer was diagnosed in 21 (4%) patients, including 4 gastrointestinal cancers. The use of IBD medication was comparable between Eastern and Western European centres apart from 5-aminosalicylic acid agents (Table 1). During follow-up, 60 out of 360 patients (17%) progressed from non-stricturing-non-penetrating disease (B1) at diagnosis to stricturing or penetrating disease (B2 or B3) while 13 out of 83 patients (16%) with stricturing disease (B2) progressed to penetrating disease (B3). The median time to progression was 28 (IQR: 9-64) months from diagnosis. No patients from Eastern Europe were exposed to biological therapy prior to change in behaviour, compared to 23 out of 66 patients (35%) from Western Europe. Multivariate Cox regression analysis showed no difference in risk of surgery according to European region (Eastern vs. Western Europe, HR: 0.54, 95%CI: 0.24-1.21). Early intervention with biological therapy (within 6 months) did not influence the risk of surgery (HR:0.75, 95%CI: 0.31-1.83), however early introduction of immunomodulators reduced the risk significantly (HR:0.54, 95%CI: 0.30-0.98). Progression in behaviour from B1 was associated with higher risk of surgery (HR:7.62, 95%CI: 3.91-14.87). Conclusion: After 10 years of follow-up, 21% underwent intestinal resection and 10% required additional resections. Despite the widespread use of immunomodulators and biological therapy, 16% of the patients had disease behavioural progression, which was associated with higher risk of surgery. Early introduction of immunomodulators was found to be beneficial.